An imine-containing epoxy vitrimer with versatile recyclability and its application in fully recyclable carbon fiber reinforced composites. (20th October 2020) - Memon, Hafeezulah; Wei, Yi; Zhang, Liying; Jiang, Qiuran; Liu, Wanshuang
Abstract: Environmental economics is accelerating the urgency to develop recycling technologies for the ever-growing quantity of discarded carbon fiber reinforced polymer composites (CFRCs). Herein, an imine-containing epoxy hardener (ICH) was synthesized by condensation of lignin-derived vanillin and methylcyclohexanediamine. The epoxy resin (vitrimer) cured by ICH has sufficient glass transition temperature (≥131 °C), tensile strength (≥82 MPa) and solvent resistance. The incorporated dynamic imine bonds allow the epoxy resin to be reprocessable and degradable. The reprocessed resin has slightly increased glass transition temperature ( T g ) and around 90% retention rate of tensile strength. Besides, the imine-containing epoxy resin can be chemically recycled in a closed-loop manner by two different methods. Among them, one recycled epoxy resin almost obtains a full recovery in terms of tensile strength and T g . The CFRCs based on the ICH cured epoxy resin exhibit comparable flexural properties compared to those based on conventional epoxy resins. The vitrimer feature of the ICH cured epoxy resin enables the CFRCs to be repairable. Especially, 92% strength recovery is achieved for the repaired CFRCs after interlaminar shear failure. Furthermore, nondestructive carbon fibers are recovered from CFRCs by degrading the matrix resin in an amine solvent, and the degradation products can be re-used to prepare new epoxy resins, thus achieving a full recycling process for CFRCs. We believe the findings in this work would provide a promising solution for the recycling of CFRCs. Graphical abstract: Image 1 Highlights: An imine-containing epoxy resin with high performance and versatile recyclability. The recycled epoxy resins show high performance retention rate. Closed-loop recycling of carbon fiber reinforced epoxy composites.